The Resilience of Coffee Roastery in the Downtown Area; Case Study of The Coffee Lab Dubai - Kurniawan Arif Maspul (JURNAL PURNAMA BERAZAM, 2021)
The vast number of coffee roasteries opened in Dubai is a unique highlight of how regulations serve, following how sustainability impacts society. The author performed this case study based on data pertained as a coffee roaster at The Coffee Lab Dubai. Delineated qualitatively and revealed the retail resilience of The Coffee Lab as one of the most sustainable businesses in the UAE. In this case study, the author used to collect the data from the work area at The Coffee Lab, such as coffee production and all things related to the business establishment since its opening until March 23, 2020. Since the first day of work, the author collected the data and recorded manually through the Microsoft Excel for the actual numbers in daily closing, especially in coffeeshop's consumption. The author is the certified Person in Charge (PIC) of The Coffee Lab and Authorized Specialty Coffee Association Trainer (AST) for roasting. The Coffee Lab used to do more production in roasting and has been continuously supplied an enormous number of coffee shops in the UAE and the GCC countries. By March 2020, the show reached an average of 1.2 tons/month. Using the Loring F15, saving the emission of gas more than the usual coffee roaster machine, the capacity of 15kg was quite good enough for daily production from 70 -200kg. Meanwhile, the most important of the coffee roastery as well as the plan of Hazard Analysis Critical Control Path (HACCP), which should be well-approved by the Dubai Municipality Coffee production, specifically roasting, has long fallen under the radar when it comes to food safety concerns at manufacturing facilities, and for the coffee roasters who operated them. Anyone who helped set up or maintain written food safety plans for a roasting operation knows that one of the critical elements is a Hazard Analysis Critical Control Path (HACCP) plan." (Ebert, 2017) One of the examples is The Coffee Lab which is located in the Port Rashid region, which is unique compared to coffee roasteries in the UAE, where many coffee roasteries are established in industrial areas to protect the environment and community safety. The Coffee Lab maintains online sales through e-commerce service with an average of 10-30 orders daily for roasted coffee sales or accessories for personal or business to business consumption. The coffee roastery is trying to keep the resilience to bring the green coffee from farmers as a producer and doing production in roasting and maintain its existence to continue and develop the business in the downtown area out of the industrial city. The coffee roastery itself has been run for the past three years and still growing with a good number of daily production year to year.